Analysis of Current Situation Regarding Scientific Fitness Literacy of Nurses in Sports Medicine Integration - Liu, Juan; Wang, Yan; Shi, Xiao-Yang; Liu, Xin-Yu; Cui, Cai-Hong; Qin, Liang; Wei, Qi-Xuan; Niu, Zong-Bao (Risk management and healthcare policy, 2022)
Objective: The present study aims to analyze the current situation of scientific fitness literacy in nurses and provide a basis for all-round strategies for its improvement. Methods: Nurses in tertiary hospitals were conveniently selected as subjects in order to investigate the current situation regarding the scientific fitness literacy of nurses. The selection process was completed via the demographics questionnaire and the adult scale of scientific fitness literacy in sports medicine integration. As the minimum sample size was 5-10 times the number of variables in the study of exploring influencing factors of related variables and using the equation N =[numberofvariablesx(5 10)]x'1 + 10%], given 20% of invalid questionnaires, the sample size should be >600 persons. The methods used for statistical analysis were descriptive statistical analysis and the t-test. Results: The scientific fitness literacy score in nurses was 110.81 [+ or -] 25.04 (relative value: 69.7%); this consisted of 50.85 [+ or -] 11.19 (73.7%) for scientific fitness knowledge dimension, 25.99 [+ or -] 5.35 (78.8%) for scientific fitness attitude dimension, and 33.97 [+ or -] 13.59 (59.6%) for scientific fitness behavior and skill dimension. The results of the independent sample t-test and analysis of variance showed that the differences in gender, education level, position, exercise habits, and balanced diet in daily life among nurses (regarding scientific fitness literacy) were statistically significant (P < 0.05). Conclusion: Nurses generally have an above-average level of scientific fitness literacy; this is mainly due to their good cognition and attitude regarding scientific fitness. However, their scientific fitness behaviors and skills are greatly inadequate. They are especially weak in completing WHO's recommended amount of exercise, mastering the cores of sports skills, undergoing a professional assessment before exercise, and developing exercise plans. Keywords: sports medicine, nurses, scientific fitness, literacy, situation